Simulation of phase diagrams in LaNi₅-H₂(D₂) system and inversion of isotopic effect - Marinin, V.S.; Shmalko, Yu.F.; Umerenkova, K.R. (Functional Materials, 2007)
Simulation of phase transitions in IMC-hydrogen systems based on modified scheme of perturbation theory provides correct description of main characteristics of phase diagrams within a wide pressure range of hydrogen isotopes (6 decimal orders and wider). The obtained data on thermodynamic parameters of α-β transition allows to describe inversion of isotopic effect in LaNi₅-H₂(D₂) system. Data on solubility of hydrogen isotopes in LaNi₅ at pressures up to 500 atm. have been obtained; data on parameters of the critical points of α-β equilibrium (for which experimental data are absent) have been also obtained. The proposed calculation scheme does not use any fitting parameters or empirical correlations and is based on atomic characteristics of the hydrogen subsystem and metallic matrix which are physically meaningful.